Studi Pola Segregasi Karakter Morfologi – Agronomi Tanaman Padi Hasil Persilangan Kultivar Pandan Ungu x Roti Pada F2 - cristabel elisa; syamad ramayana; rusdiansyah rusdiansyah (Mulawarman University, 2019)
Abstract. The efforts to increase rice production at East Borneo apart from the improvement of cultivation systems also could be done by using superior variety. Hybridization of rice plants has been done between the female local variety Pandan Ungu and the male local variety Roti. The research toward F2 progeny to find out the segregation patterns of inheritance of the characters number of tillers, plant height, stem leaves color, and palea-lemma color has been done at the paddy field at Desa Sidomulyo, Kecamatan Anggana, Kabupaten Kutai Kartanegara since October 2016 until March 2017. The F2 identification method that was used is single plant selection methods, based on Standard Evaluation Systems (SES) for Rice. Suitability test between observed value and expected value used Chi-square test, and to see the characters segregation pattern ratio used Mendelian genetics analysis. The inheritance character of stem leaves color was managed by two pairs of genes followed segregation ratio 9:6:1 with the action epistatic genes with cumulative effect, the inheritance of palea-lemma character was managed by two pairs of genes followed Mendelian ratio 13:3 with the action epistatic dominant-recessive, while the characters plant height and number of tillers was managed by polygenes so the inheritance patterns was not following Mendelian ratio.